2015
DOI: 10.1245/s10434-015-4521-4
|View full text |Cite
|
Sign up to set email alerts
|

Do All Patients Require Prophylactic Drainage After Gastrectomy for Gastric Cancer? The Experience of a High-Volume Center

Abstract: Not using a PD increased the risk of PCD postoperatively, but no microbes in peritoneal fluid were detected in the most patients. Selective use of PD in patients during gastric cancer surgery may be possible using our risk factor analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Unfortunately, we found no other new RCT nor meta‐analyses concerning abdominal drain placement after gastrectomy. Although we did find several retrospective analysis papers published after 2014, they all suggested that abdominal drain placement was unnecessary or only necessary in high‐risk cases …”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomymentioning
confidence: 88%
“…Unfortunately, we found no other new RCT nor meta‐analyses concerning abdominal drain placement after gastrectomy. Although we did find several retrospective analysis papers published after 2014, they all suggested that abdominal drain placement was unnecessary or only necessary in high‐risk cases …”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomymentioning
confidence: 88%
“…The use of abdominal drains following gastrectomy still remains controversial. Prophylactic peritoneal drainage has been widely used during gastrointestinal surgery because of several advantages such as removing intraperitoneal fluid and assisting the early detection of postoperative hemorrhage or anastomotic leakage [ 31 33 ]. However, peritoneal drainage can cause uncomfortable which may limit early mobilization and postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Although avoiding the use of abdominal drains is recommended in the guidelines for ERAS after gastrectomy, 22 the risk of percutaneous abdominal drainage may be increased without abdominal drain insertion. 33 In addition, abdominal drain placement following gastrectomy may not affect the length of hospital stay, 34 suggesting that it is not necessary to avoid using an abdominal drain. Prospective randomized studies providing high-quality evidence should evaluate the significance of abdominal drains following gastrectomy.…”
Section: Discussionmentioning
confidence: 99%